2019
DOI: 10.1038/s41598-019-46842-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of acetylcholinesterase 1 in response to various stress factors in honey bee workers

Abstract: The honey bee acetylcholinesterase 1 (AmAChE1) has been suggested to be related to stress response as judged from its elevated expression level under brood rearing-suppressed conditions. To further investigate the involvement of AmAChE1 expression in the stress response and its physiological functions, we analyzed altered expression profiles of AmAChE1 induced by diverse stress factors. In addition, transcription profiles of several heat shock protein (Hsp) genes ( hsps ) and the vitello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 57 publications
3
20
1
Order By: Relevance
“…Bees not only respond to heat stress through behavioral changes, they also enhance their heat resistance by gene expression regulation. Under heat stress, bees induce the expression of many key genes and proteins, including Hsp, NF-Y, acetylcholinesterase 1 (AchE1), and zinc finger protein (ZFP) (Figure 1b) (Kim et al 2019;Li et al 2020a, b;Ma et al 2019;Zhang et al 2014). In addition, heat stress can cause the production of reactive oxygen species (ROS).…”
Section: Molecular Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…Bees not only respond to heat stress through behavioral changes, they also enhance their heat resistance by gene expression regulation. Under heat stress, bees induce the expression of many key genes and proteins, including Hsp, NF-Y, acetylcholinesterase 1 (AchE1), and zinc finger protein (ZFP) (Figure 1b) (Kim et al 2019;Li et al 2020a, b;Ma et al 2019;Zhang et al 2014). In addition, heat stress can cause the production of reactive oxygen species (ROS).…”
Section: Molecular Levelmentioning
confidence: 99%
“…Bees cannot bear this degree of heat stress and will die oxidative damage and enhancing antioxidant ability (Figure 2) (Li et al 2020b). In addition, a recent study reported that the expression of honeybee AChE1 is significantly induced by heat stress, and this induction degree is more apparent in the abdomen than in the head (Kim et al 2019). A recent transcriptome study showed that the mRNA levels of ZFP (such as ZFP271 , ZFP37 , ZFP239 , ZFP776 , and ZFP93 ) and serine/ threonine protein kinase (STK ) (such as STK-6 ) are regulated by high temperatures, indicating that they may function in the response of bees to heat stress (Ma et al 2019).…”
Section: The Functions Of Other Genes In Bee Heat Stress Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnson et al 2013; Straub et al 2019). Identification of suitable biomarkers for the prior detection of stress in honey bee colonies, therefore, becomes crucial for proactive management (Kim et al 2019). Various biomolecules including glutathione-S-transferase, acetylcholinesterase (AChE), metallothioneins, alkaline phosphatase, nicotinic acetylcholine receptors (nAChRs), cytochrome P450 oxidase, vitellogenin and α-tocopherol are used to assess the effects of diverse stressors in honey bees (Badiou-Bénéteau et al 2013; Christen & Fent 2017; Gauthier et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Various biomolecules including glutathione-S-transferase, acetylcholinesterase (AChE), metallothioneins, alkaline phosphatase, nicotinic acetylcholine receptors (nAChRs), cytochrome P450 oxidase, vitellogenin and α-tocopherol are used to assess the effects of diverse stressors in honey bees (Badiou-Bénéteau et al 2013;Christen & Fent 2017;Gauthier et al 2018). Enzymatic biomarker, AChE is targeted as a promising candidate, because of its vulnerability to express differentially in relation to the pesticide exposure (Boily et al 2013; but see Kim et al 2019), seasonal condition (Kim et al 2017), landscape (Badiou-Bénéteau et al 2013) and nutrition status (Kim et al 2017(Kim et al , 2019. AChE rapidly hydrolyses ACh at the cholinergic synapses, thus allowing precise control and modulation of the neural transmission (Badiou et al 2008).…”
Section: Introductionmentioning
confidence: 99%